1999
DOI: 10.1080/14017439950141425
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Serial Changes in Left-sided Heart Chambers and Atrial Natriuretic Peptide and N-terminal Pro Atrial Natriuretic Peptide after a First Myocardial Infarction: An Echocardiographic Study

Abstract: Dilatation of the left ventricle predicts morbidity and mortality after acute myocardial infarction. We compared serial echocardiographic examinations of the left atrium and ventricle with measurements of plasma atrial natriuretic peptide (ANP) and plasma N-terminal pro atrial natriuretic peptide (NT-proANP) in 22 patients during the first 6 months following a first myocardial infarction. ANP, but not NT-proANP, was found to be significantly correlated to the diastolic/systolic size of the left atrium (r = 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Postoperative symptomatic improvement following surgery for aortic stenosis may be predicted using left atrial size 1. An echocardiographic study2 found a significant correlation between left atrial size and atrial natriuretic peptide levels after acute myocardial infarction both at 10 to 12 days post infarction as well as at six months. Based on a correlation coefficient of 0.70, it was concluded that the percentage change in the size of the left atrium could reliably predict the percentage change in atrial natriuretic peptide after an acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative symptomatic improvement following surgery for aortic stenosis may be predicted using left atrial size 1. An echocardiographic study2 found a significant correlation between left atrial size and atrial natriuretic peptide levels after acute myocardial infarction both at 10 to 12 days post infarction as well as at six months. Based on a correlation coefficient of 0.70, it was concluded that the percentage change in the size of the left atrium could reliably predict the percentage change in atrial natriuretic peptide after an acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The approximate ANP plasma half-time is approximately 2–3 min. Released in equimolar amounts NT-proANP, slowly eliminated by kidneys, appears to have more practical diagnostic use [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%